Determination of the Radiation Dose Level in Different Slice Computerized Tomography - GÜNAY, Osman; GÜNDOĞDU, Özcan; DEMİR, Mustafa and ABUQBEİTAH, Mohammad and YAŞAR, Doğan and AKÖZCAN, Serpil and KAPDAN, Enis and YARAR, Onur (International Journal of Computational and Experimental Science and Engineering, 2019)
Today, many imaging tools have emerged in the medical field using ionizing radiation. Computed tomography (CT) is regarded the most creative and common modality among the other imaging devices. In CT imaging, radiation may scatter to the environment from the patient and the interaction medium. In this study, two CT scanners with different slice numbers were used to measure the scatter radiation dose to the environment. Alderson rando phantom was utilized in the acquired CT exams as human body simulation. Radiation dose levels at different distances were determined by placing thermoluminescence dosimeters in the surrounding environment (at different distances) during phantom’s head-neck and thorax CT imaging. As a result, it has been found that the radiation dose varies between 13.90±1.96 µSv and 96.79±11.12 µSv in head and neck CT imaging. While, in thorax CT scan, the radiation dose varies between 5.28±0.84 µSv and 20.63±1.76 µSv.